Landscape Design of the Urban Environment: Ecological Aspects - Shevchenko, Liudmyla; Novoselchuk, Nataly; Toporkov, Volodymyr; Kuznietsova, Yana (International Journal of Engineering and Technology, 2018)
This article is aimed to consider some aspects of the landscape design of the urban environment, oriented to recreate its natural ecological balance and provide esthetically attractive and healthy living environment. The authors emphasize the importance of creation of a harmonious environmentally friendly urban environment for vital activity of its habitants basing on the proper collaboration of natural and anthropogenic constituents. Approaches and methods, that formed the basis of algorithm of this research and facilitated the careful analysis of the available historiography material, urban environment world analogues, their project design are represented. The authors gave a conceptual framework, that consists of the terms related to this research by content. Aspects of landscape design of urban environment are outlined. The authors focused their particular attentionÂ to the educed ways of solutions of the ecological problems of the urban environment by means of landscape design - by forming the ecological framework of a city; creation of the environmental architecture; recourse of the verdured roofs and walls; by ecologization of transport arteries, introduction of bike paths, application of eco-grades, parklets; by creation of walking paths, sites and small architectural forms, without impact on natural form of earth and areas of the existent planting. It is to be noted that the proper approach to the landscape design of an urban environment is the powerful motivator for improvement of ecological situation, creating accents wherein they have been set by nature. It is highlighted that only the all-round consideration of features of natural urban environment can assist creation of a perfect ecological landscape at the urban framework, its layout structures and infrastructures as a whole.Â Â Â